а) z* = -z·i
z = x + iy
x - iy = -(x + iy)·i
x - iy = -ix + y
x + ix = y + iy
x·(1 + i) = y·(1 + i)
y = x
z = x + ix, x ∈ R
б) 2·|z| - 8z + 1 + 2i = 0
z = x + iy
2√(x² + y²) - 8·(x + iy) + 1 + 2i = 0
2√(x² + y²) - 8x - i8y + 1 + 2i = 0
2√(x² + y²) = (8x - 1) + i(8y - 2)
2√(x² + y²) = 8x - 1
8y - 2 = 0
y = 1/4
2√(x² + (1/4)²) = 8x - 1
4(x² + 1/16) = 64x² - 16x + 1
8x - 1 ≥ 1/2
4x² + 1/4 = 64x² - 16x + 1
8x ≥ 3/2
60x² - 16x + 3/4 = 0
x ≥ 3/16
240x² - 64x + 3 = 0
D = 64² - 4·240·3 = 1216
x = (64 (+/-) √1216)/480 = (64 (+/-) 8√19)/480 = (8 (+/-) √19)/60
x = 2/15 (+/-) √19/60
x ≥ 3/16
x = 2/15 + √19/60
z = 2/15 + √19/60 + i/4
а) z* = -z·i
z = x + iy
x - iy = -(x + iy)·i
x - iy = -ix + y
x + ix = y + iy
x·(1 + i) = y·(1 + i)
y = x
z = x + ix, x ∈ R
б) 2·|z| - 8z + 1 + 2i = 0
z = x + iy
2√(x² + y²) - 8·(x + iy) + 1 + 2i = 0
2√(x² + y²) - 8x - i8y + 1 + 2i = 0
2√(x² + y²) = (8x - 1) + i(8y - 2)
2√(x² + y²) = 8x - 1
8y - 2 = 0
y = 1/4
2√(x² + (1/4)²) = 8x - 1
4(x² + 1/16) = 64x² - 16x + 1
8x - 1 ≥ 1/2
4x² + 1/4 = 64x² - 16x + 1
8x ≥ 3/2
60x² - 16x + 3/4 = 0
x ≥ 3/16
240x² - 64x + 3 = 0
D = 64² - 4·240·3 = 1216
x = (64 (+/-) √1216)/480 = (64 (+/-) 8√19)/480 = (8 (+/-) √19)/60
x = 2/15 (+/-) √19/60
x ≥ 3/16
x = 2/15 + √19/60
z = 2/15 + √19/60 + i/4
ответ: а₁=11; n=5.
Объяснение:
а n=а₁+d(n-1); 23=а₁+3(n-1); а₁=23-3n+3; а₁=26-3n.
Sn= (2а₁+d(n-1)):2*n; 85=(2а₁+3n-3)):2*n; 2а₁n+3n²-3n=170;
Подставим значение а₁ в уравнение суммы:
2n(26-3n)+3n²-3n-170=0;
52n-6n²+3n²-3n-170=0;
-3n²+49n-170=0;
3n²-49n+170=0;
D= 49²-4*3*170=2401-2040=361=19²;
n₁₂=(49±19):6;
n₁ =(49+19):6=68:6=11,3; n∉N ⇒не удовлетворяет смыслу задачи.
n₂=(49-19):6=30:6=5.
а₁=26-3n=26-3*5=26-15=11.
ответ: а₁=11; n=5.